2016
DOI: 10.1111/poms.12539
|View full text |Cite
|
Sign up to set email alerts
|

The S‐Curve Effect of Lean Implementation

Abstract: T here is currently no theory that explains the pattern of change in a plant's performance as it implements a lean program. Does it improve at a declining, increasing, or constant rate, or in some other pattern? We use empirical data from the implementation of the Volvo Group's lean program worldwide to develop a grounded theory to explain this pattern. We find that the pattern roughly follows an S-curve shape: as a plant progresses in its implementation of lean production, its operational performance improves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 57 publications
8
96
0
3
Order By: Relevance
“…For example, in their study of organizational learning in two electronic equipment manufacturers, Adler and Clark (1991) found that systematic learning efforts initially reduced productivity. Similarly, studying PI in automobile plants, Netland and Ferdows (2016) found that plant productivity worsened initially before improving. Nembhard and Tucker (2011) studied deliberate learning activities (DLAs) used for improving existing work practices in hospitals and found evidence of an initial dip in performance before turning around.…”
Section: Problem Situation (S) Methodology (M) and Theory Refinemenmentioning
confidence: 97%
“…For example, in their study of organizational learning in two electronic equipment manufacturers, Adler and Clark (1991) found that systematic learning efforts initially reduced productivity. Similarly, studying PI in automobile plants, Netland and Ferdows (2016) found that plant productivity worsened initially before improving. Nembhard and Tucker (2011) studied deliberate learning activities (DLAs) used for improving existing work practices in hospitals and found evidence of an initial dip in performance before turning around.…”
Section: Problem Situation (S) Methodology (M) and Theory Refinemenmentioning
confidence: 97%
“…'Lean' is a philosophy built around 'waste minimization'. It is administered by imbibing a 'bundle of practices' which aim endlessly to achieve higher levels of resource efficiency in the system and try to culminate any non-value added activities (Carvalho et al, 2011;Netland & Ferdows, 2016). Various researchers have explored lean practices and their impact on the sustainable performance of a firm.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the time required to rollout initiatives and efficiencies realized from learning by doing, we anticipate that the effectiveness of an OPX will increase with its length of operation. Netland and Ferdows () observed a similar trend towards improved effectiveness over time, when studying the implementation of lean programs at 45 Volvo plants. Taken together, these arguments suggest that an OPX is likely to improve EQ, its effectiveness improving over time.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 68%